DETERMINATION OF INTEGRATED ENVIRONMENTAL INDICATORS OF THE IMPACT OF POLLUTANTS INTO WATER BODIES - V. Filipova, Margarita (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The advantages and disadvantages of the current limit concentrations (PDC) have been analysed as they do not fully reflect the impact of alien substances on water in aquatic ecosystems. A relatively simple method for determining integral doses in multifactorial contamination of water bodies has been proposed.